HUBUNGAN PENDIDIKAN, PENGETAHUAN, DAN PERILAKU IBU TERHADAP STATUS KARIES GIGI BALITANYA: RELATIONSHIP BETWEEN EDUCATION, KNOWLEDGE, AND MOTHER'S BEHAVIOUR TOWARD DENTAL CARIES STATUS OF HER UNDER FIVE YEARS OLD CHILDREN - Lina Natamiharja,; Nila Silvana Dewi, (Dentika: Dental Journal, 2010)
Children whose mother’s have low education level have higher caries risk compared to children whose mother’s have high education level. Besides mother’s education, mothers behavior about dental health such as frequency of tooth brushing and sweet food consumption also has significant relation with the caries status of her child aged 1-5 years old. This study was conducted to know the relationship between education, knowledge and mother’s behavior about child dental health care with the prevalence of free caries and def-t of the child. Population were mothers and their children aged 3-4 years taken from 4 play groups and 2 BKIA (welfare of mother and child department) Medan Selayang District, Sample size was counted with formula of cross-sectional study design as many as 140 subjects. Data collection was done by clinical examination on the children and interviewed the mothers. Data analysis was done with Anova and Chi square test. The results showed that 65% children had dental caries. There were significant relationships between mother’s education level with the prevalence of the caries (p= 0.001) and the def-t (p= 0.001) ; between mother’s knowledge and the prevalence of free caries (p= 0.013) and the mean of def-t (p= 0.004) ; and there were also significant differences between mother’s behaviour with the prevalence of free caries (p=0.01) and the mean of def-t (p= 0.000). It can be concluded there were significant relationships between education, knowledge and mother behavior level with the prevalence of the caries and the mean of def-t.